2018
DOI: 10.1093/advances/nmx009
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate: A Double-Edged Sword for Health?

Abstract: Butyrate, a four-carbon short-chain fatty acid, is produced through microbial fermentation of dietary fibers in the lower intestinal tract. Endogenous butyrate production, delivery, and absorption by colonocytes have been well documented. Butyrate exerts its functions by acting as a histone deacetylase (HDAC) inhibitor or signaling through several G protein-coupled receptors (GPCRs). Recently, butyrate has received particular attention for its beneficial effects on intestinal homeostasis and energy metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
605
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 768 publications
(637 citation statements)
references
References 128 publications
21
605
0
11
Order By: Relevance
“…Furthermore, an age‐ and sex‐matched study showed that the population of the genera Faecalibacterium was decreased significantly in PPI users . As a product of Faecalibacterium , butyrate could enhance intestinal barrier function and mucosal immunity, which might prevent translocation of enteric bacteria into the peritoneal cavity . Third, GASs might impair the function of immune cells against bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an age‐ and sex‐matched study showed that the population of the genera Faecalibacterium was decreased significantly in PPI users . As a product of Faecalibacterium , butyrate could enhance intestinal barrier function and mucosal immunity, which might prevent translocation of enteric bacteria into the peritoneal cavity . Third, GASs might impair the function of immune cells against bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…40 As a product of Faecalibacterium, butyrate could enhance intestinal barrier function and mucosal immunity, which might prevent translocation of enteric bacteria into the peritoneal cavity. 41 Third, GASs might impair the function of immune cells against bacterial translocation. Haas In subgroups based on use of different types of GASs, a metaanalysis by Khan and colleagues on patients with cirrhosis demonstrated that H 2 RAs (OR = 1.93; 95% CI: 1.15-3.24, I 2 = 0%) and…”
Section: Recent Meta-analyses On Patients With Cirrhosis Demonstratedmentioning
confidence: 99%
“…It increases the mitochondrial respiration rate and ATP production. Butyrate is a histone deacetylase inhibitor that induces the sprouting of dendrites, increases the number of synapses, and reinstates learning behavior and access to long‐term memories . Butyrate can facilitate increased gut intestine motility by stimulating cholinergic neurons of the ENS, whereas propionate decreases motility and increases secretion.…”
Section: Intestinal Microbiome Neurodevelopment and Neuroinflammationmentioning
confidence: 99%
“…A comprehensive review has clearly explained the role of amino acids in gut‐microbiome immune crosstalk, which improves the intestinal homeostasis . Other related studies on pig models showed that the use of sodium butyrate and moderate dietary protein to control weaning diarrhea improves ileal barrier function . Previous studies reported that the whole microalgal biomass can be used as an animal feed supplement .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Other related studies on pig models showed that the use of sodium butyrate and moderate dietary protein to control weaning diarrhea improves ileal barrier function. [11][12][13] Previous studies reported that the whole microalgal biomass can be used as an animal feed supplement. [14][15][16] The use of whole biomass as food supplementation has been studied in rodents, and has shown improved serum lipid profile, omega-3 index, and erythrocyte plasticity.…”
Section: Introductionmentioning
confidence: 99%